Pengaruh Persepsi Pelaku UMKM, Tingkat Pendidikan dan Sosialisasi SAK EMKM terhadap Penerapan SAK EMKM - Odha, RaodahtulJannah; Ismawati; Muchlis, Saiful (PT Bone Jaya Kreatif, 2023)
This study aims to determine the effect of the perceptions of MSME actors, level of education and socialization of SAK EMKM on the application of SAK EMKM (Study in Samata sub-district, Gowa district). This research is a quantitative research with a positivist research approach. The population in this study were SMEs in the Samata village, Gowa Regency. The sampling technique in this study was purposive sampling, while the samples in this study were MSME actors in Samata Village, Gowa Regency. The data collection method is using a questionnaire that is distributed directly. The data used in this study is primary data collected through a questionnaire survey. Data analysis used statistical analysis to determine the effect of the perceptions of MSME actors, education level and socialization of SAK EMKM on the implementation of SAK EMKM. The results of this study indicate that the perceptions of MSME actors, level of education and socialization of SAK EMKM greatly influence the implementation of SAK EMKM.